Contaminant management in water reuse systems - Qadir, Manzoor; Drechsel, Pay (2016)
Although wastewater has been increasingly used to grow a range of crops for income generation and livelihood resilience in urban and peri-urban areas, irrigation with untreated or partially treated wastewater may result in negative impacts on irrigated crops, soils, and groundwater along with implications for human and environmental health through chemical and microbial risks. With the potential for environmental risks due to concentrations above the maximum allowable levels, the major chemical constituent groups that need to be addressed in wastewater-irrigated environments are metals and metalloids, essential nutrients, salts and specific ionic species, and persistent organic pollutants. To avoid potential negative impacts, conventional wastewater treatment options, which can control the release of these contaminants into the environment, remain the key to protecting water quality for beneficial uses in agriculture, aquaculture, and agroforestry systems. Effective legislation, monitoring, and enforcement are also essential and often neglected management strategies. At the farm level, some low-cost irrigation, soil, and crop management options, discussed in this chapter, are available to reduce the risk from contaminants added through wastewater irrigation.